Effectiveness Of Public Complaint Services at RSUD R.T. Notopuro Sidoarjo - Elisa Pingky Vernanda; Lukman Arif (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The current condition of public services is facing various significant challenges and opportunities. Public services include various types of services provided by the government, one of which is services in the health sector. RSUD R.T. Notopuro Sidoarjo is a type A hospital, in providing services there are still problems such as long queues, slow service and lack of human resources, which are the main obstacles. This study uses a qualitative method with a descriptive research type. Data collection techniques include observation, interviews, documentation. The results of this study indicate that the effectiveness of public complaint services at RSUD R.T. Notopuro Sidoarjo is said to be successful, can be stated as follows by 1) High productivity in handling complaints, shown by the number of staff and complaints resolved within a certain period. 2) Efficient service through fast response times once complaints are received. 3) Quality of service marked by consistency and transparency in complaint handling. 4) Flexibility in offering multiple channels for submitting complaints and adaptive policies. 5) Development of the complaint system is progressing well, supported by sufficient resources and effective use of information technology. 6) Public satisfaction is relatively high, especially in terms of complaint resolution, though some units still require improvement. 7) Service excellence is reflected in overall quality improvements.